PENGOLAHAN MODEL KECEPATAN MENGGUNAKAN METODE RAY TRACING UNTUK MIGRASI DOMAIN KEDALAMAN (PRE STACK DEPTH MIGRATION) 2D PADA LAPANGAN “AV” - Anjar Evita; Hernowo Danusaputro; Muhammad Mualimin (Youngster Physics Journal, 2014)
The research was done to process 2D seismic data by Pre Stack Depth Migration (PSDM) method on Field “AV”. The purpose of this study was to determine the appropriate interval velocity model for PSDM methods work. Interval velocity model obtained from the initial estimate using coherency inversion velocity model is usually not convergent. Interval velocity model should be improved through several stages in order to speed the estimated value closer to the value of actual speed. Some initial interval velocity model parameters should be improved to be more sensitive to lateral velocity variations for PSDM. The method used to improve the velocity model is horizon-based tomography with the concept of ray tracing. These methods made improvements to the speed and geometry of the reflector layer to produce a new interval velocity model. Model errors must be corrected by residual moveout analysis. The best analysis obtained from the fifth iteration to eliminated errors and increased depth value gathers. The exact value of the speed made a good quality image. The results of this research was PSDM Section or PSDM cross-section. The quality of PSDM cross-section was good enough to represented geological structures in the earth's sub surface.Keywords: PSDM, interval velocity model, horizon-based tomography, ray tracing, residual moveout analysis.